'A journalism of fear'. (August 2021) - Anderson, Chris W
What should journalism do, and for what reasons should it do it? The starting point of this article is that two distinct but converging factors have made this question increasingly hard to answer. On one hand, the seemingly perpetual crisis in newsroom capacity has made it hard to sustain a maximalist normative conception of what journalism should accomplish. On the other hand, the globalization of journalism studies research has problematized the assumed link between journalism and democracy. In response, this article outlines a new normative journalistic ideal, grounded in the political theory of the late Judith Shklar – a 'journalism of fear'. Under this model, the link between journalism and liberalism is asserted over and above the link between journalism and democracy. Drawing on Shklar, the journalism of fear contends that the worst of all evils is cruelty, and the purpose of journalism is to minimize that cruelty. The article elaborates Shklar's thinking by comparing her perspective on a number of issues to those of a far more familiar political philosopher, John Dewey. It concludes by looking at what a journalism of fear would look like in practice by briefly discussing newsroom responses to the Windrush scandal in the United Kingdom.